1997
DOI: 10.1177/030006059702500408
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole Treatment of Neonates and Infants with Severe Fungal Infections

Abstract: A total of 24 neonates and infants, aged from 2 days to 10 months, received treatment with intravenous fluconazole for microbiologically documented or presumed fungal infection. The mean fluconazole dosage was 6 mg/kg/day (range 2-16 mg/kg/day) and the mean duration of therapy was 25 days (range 5-72 days). Efficacy was evaluated in neonates with proven fungal infections, as documented by the presence of pathogen at baseline. A positive clinical response was achieved in 23 of the 24 clinically evaluable patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…It was reported that fluconazole appears to be safe and effective for treatment of systemic candidal infection in children. 32,33 Randomised-controlled trials support its use in the treatment of candidaemia, showing equivalent efficacy and a superior safety profile compared with amphotericin B. 34 Our results were similar to those reported by other authors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was reported that fluconazole appears to be safe and effective for treatment of systemic candidal infection in children. 32,33 Randomised-controlled trials support its use in the treatment of candidaemia, showing equivalent efficacy and a superior safety profile compared with amphotericin B. 34 Our results were similar to those reported by other authors.…”
Section: Discussionsupporting
confidence: 86%
“…Also, there was significantly different in mean length of hospitalisation before onset of the candidaemia among patients with C. albicans (23.6 days) and non-albicans species (17.0 days) (P = 0.01). Mean gestational age of neonates was 31.2 ± 5.3 weeks (range: [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Seventy-two per cent were premature newborns.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in pediatric age group indicate that fluconazole is effective and safe in treatment of Candidemia. Accordingly, 40.6% of the patients in our study group were treated with fluconazole only as the first line of the treatment [18,19]. Additionally, 26.2% of the patients which had febrile neutropenia were treated with amphotericin B, while 15.3% received caspofungin, 9.6% received voriconazole, and 2.6% who had neonatal meningitis were treated with amphotericin B + flucytosine.…”
Section: Discussionmentioning
confidence: 97%
“…Its favorable pharmacokinetic features include good penetration into the CSF, a high concentration of active drug in the urine and minimal toxicity 13,15 . Thus fluconazole appears to have an excellent safety profile for children 16 . We chose the combination of amphotericin B deoxycholate and fluconazole.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Thus fluconazole appears to have an excellent safety profile for children. 16 We chose the combination of amphotericin B deoxycholate and fluconazole. After initiating this regimen, our patient showed marked clinical improvement.…”
Section: Discussionmentioning
confidence: 99%